Oceans - Brown, Carron; Thorns, Becky (Tulsa, OK : Kane Miller, a division of EDC Publishing, 2021)
"From the sunlit surface, to the deep, dark depths, Shine-a-Light Oceans dives into life beneath the waves. Readers will meet amazing animals from each of Earth's five oceans, including narwhals, puffins, turtles, and sharks, as well as find out about different underwater habitats and features."--from the publisher.
"Hold the page to light to see inside hidden habitats"--Cover.
Keywords: Ocean -- Juvenile literature; Marine animals -- Juvenile literature; Marine ecology -- Juvenile fiction; Toy and movable books -- Specimens; Ocean; Marine animals; Marine ecology; Toy and movable books; Fiction; Juvenile works; Specimens; Toy and movable books; Toy and movable books